Uptake and acceptability of oral HIV self-testing among community pharmacy clients in Kenya: a feasibility study - Mugo, P; Micheni, M; Shangala, J; Hussein, M; Graham, S; Rinke de Wit, T; Sanders, E (Public Library of Science, 2017)
BACKGROUND: While HIV testing and counselling is a key entry point for treatment as prevention, over half of HIV-infected adults in Kenya are unaware they are infected. Offering HIV self-testing (HST) at community pharmacies may enhance detection of undiagnosed infections. We assessed the feasibility of pharmacy-based HST in Coastal Kenya. METHODS: Staff at five pharmacies, supported by on-site research assistants, recruited adult clients (≥18 years) seeking services indicative of HIV risk. Participants were offered oral HST kits (OraQuick®) at US$1 per test. Within one week of buying a test, participants were contacted for post-test data collection and counselling. The primary outcome was test uptake, defined as the proportion of invited clients who bought tests. Views of participating pharmacy staff were solicited in feedback sessions during and after the study. RESULTS: Between November 2015 and April 2016, 463 clients were invited to participate; 174 (38%) were enrolled; and 161 (35% [95% Confidence Interval (CI) 31-39%]) bought a test. Uptake was higher among clients seeking HIV testing compared to those seeking other services (84% vs. 11%, adjusted risk ratio 6.9 [95% CI 4.9-9.8]). Only 4% of non-testers (11/302) stated inability to pay as the reason they did not take up the test. All but one tester reported the process was easy (29%) or very easy (70%). Demand for HST kits persisted after the study and participating service providers expressed interest in continuing to offer the service. CONCLUSIONS: Pharmacy HST is feasible in Kenya and may be in high demand. The uptake pattern observed suggests that a client-initiated approach is more feasible compared to pharmacy-initiated testing. Price is unlikely to be a barrier if set at about US$1 per test. Further implementation research is required to assess uptake, yield, and linkage to care on a larger scale.